Dampak Kemajuan Teknologi Pada Pendidikan Bahasa Indonesia - Resi Safira (Pusat Riset dan Inovasi Nasional, 2023)
Technology in learning is increasingly experiencing development along with the times. Often we see in the world of education a lot of use of technology as a means that can facilitate the learning process. Apart from technology education, it can also be used by the public to introduce Indonesian to foreigners. Technology can be a skill related to knowledge. This expertise can make it easier for Indonesian people to develop Indonesian. However, besides the many positive impacts that technology provides, it can also have negative impacts. The negative impact that we often encounter, for example on social media, is that many people use the Indonesian language incorrectly and not according to the rules. In fact, it is often found that young people use language immorally and ethically. Therefore this research discusses the impact of technology on language education which aims to find out what impact can be obtained from this technological development so that it can awaken many people to use Indonesian properly and according to the rules or even develop Indonesian so that it can be recognized by many. society in the world.